Clinical Study on the Effect of Moringa oleifera on Serum Level of Glucose and Tryglyceride in Subjects Taken Tenofovir, Lamivudine and Efavirenz Combination Regimen - Tosin, Joseph Opeyemi; Wolfe, Obianime A.; Iyeopu, Siminialaye M.; Simeon, Joseph Oyepata; Chinwe, Anuanwu; Lubo, Musa Tabitha (European Scientific Journal, ESJ, 2019)
Introduction/ Aim: Acquired immune deficiency syndrome (AIDS) is a disorder caused by human immune-deficiency virus. There are various life-long regimens that are currently used by HIV Patients to suppress and manage this disease. Tenofovir/Lamivudine/efavirenz (300/300/600mg) is one of the most available combinations that are frequently prescribed and dispensed to HIV patients. The aim of this clinical study is to evaluate the potential benefits of taking Moringa oleifera with Tenofovir/Lamivudine/efavirenz (TLE) on blood glucose and triglyceride level. Method: The study was designed as a Longitudinal Randomized Comparative Trial (LRCT) involving 140 HIV adult subjects (56 males, 84 females) who have been on TLE combination for at least 6 months. They were recruited from a Teaching Hospital in Nigeria. On visit 0, blood samples of the subjects were taken for analysis. Moringa oleifera capsules (200mg) were administered by the subjects to be used beginning from the day of visit 0, through visit 1 (after four weeks) and 2 (after 12 weeks). Blood samples of subjects were collected at each visit (visit 1 and 2) and analyzed for glucose and triglyceride level. Result: The analysis of each visits were compared and it was observed that there was no significant reduction in blood glucose level (P<0.01) of subjects in visit 1 compared to visit 0. There was significant improvement in blood glucose level (P<0.01) in visit 2 compared to visit 0, when subjects received tenofovir/Lamivudine/Efavirenz (TLE) combination without Moringa oleifera. It was also observed that there was no significant difference in the blood triglyceride level (P<0.01) of subjects in visit 1 and visit 2, compared to visit 0. Conclusion: Results from the study revealed that Moringa oleifera may be useful in improving blood level of glucose of patients administering TLE combination with no observable effects on triglyceride level of HIV patients on the drug regimen.